Saša Marković “From Accession to Redrawing: Vojvodina in the Kingdom of Serbs, Croats and Slovenians/Yugoslavia 1918–1941” - Vajagić, Predrag (Sociološki pregled, 2021)
The text is a critical review of the monograph by Saša Marković, the historian and professor at the Faculty of Pedagogy in Sombor. The monograph represents a synthesis of the former achievements of historiography, as well as the author’s years-long research that has resulted in many prominent scholarly works. The author’s basic intention is to offer the reader a clear and comprehensible overview of the development of political ideas in Serbian civic thought of Vojvodina during the interwar period.
Keywords: Vojvodina; accession; parliamentarism; integral Yugoslavism; redrawing; Kingdom of Serbs, Croats and Slovenians/Yugoslavia